Protein arginine methyltransferases: promising targets for cancer therapy - Hwang, Jee Won (Exp Mol Med, 2021)
Protein methylation, a post-translational modification (PTM), is observed in a wide variety of cell types from prokaryotes to eukaryotes. With recent and rapid advancements in epigenetic research, the importance of protein methylation has been highlighted. The methylation of histone proteins that contributes to the epigenetic histone code is not only dynamic but is also finely controlled by histone methyltransferases and demethylases, which are essential for the transcriptional regulation of genes. In addition, many nonhistone proteins are methylated, and these modifications govern a variety of cellular functions, including RNA processing, translation, signal transduction, DNA damage response, and the cell cycle. Recently, the importance of protein arginine methylation, especially in cell cycle regulation and DNA repair processes, has been noted. Since the dysregulation of protein arginine methylation is closely associated with cancer development, protein arginine methyltransferases (PRMTs) have garnered significant interest as novel targets for anticancer drug development. Indeed, several PRMT inhibitors are in phase 1/2 clinical trials. In this review, we discuss the biological functions of PRMTs in cancer and the current development status of PRMT inhibitors in cancer therapy.